Controlled crystallization of twinned crystalline guanine microplatelets. Issue 42 (29th August 2019) - Ma, Yurong; Chen, Fenghua; Hu, Yiran; Liu, Yanan; Qi, Limin
Abstract : In this work, twinned anhydrous guanine β microplatelets were synthesized for the first time in the presence of a polyvinylpyrrolidone. The twinning angle of the two c axes for the synthetic and biogenic twinned guanine crystals is 84°, very similar to each other. Abstract : Biogenic twinned microplatelets of the anhydrous guanine (AG) β form have been found in copepod cuticles and scallop eyes, which function as multilayer reflectors. In this work, twinned AG β microplatelets with morphologies such as cross-shape and square-shape were synthesized for the first time in the presence of a polyvinylpyrrolidone additive in formamide and water. The twinning angle of the two c diffraction vectors (84°) for the synthetic twinned guanine crystals is very similar to that of biogenic twinned guanine microplatelets observed in scallop eyes. The angles between the two observed c diffraction vectors of the synthetic twinned AG β form microplatelets were about 84° and 20°, while a twinning angle of 84° was observed in the biogenic twinned guanine microplatelets exposing the (100) face. We proposed a formation mechanism for the twinned guanine microplatelet crystals. The formation of the twinned crystals with angles of 84° and 20° between the c diffraction vectors might be related to the attachment of G-quartet molecular assemblies on the guanine plate-like crystals with a certain angle at the early stage of crystallization.